MiR‐940 inhibits hepatocellular carcinoma growth and correlates with prognosis of hepatocellular carcinoma patients. Issue 7 (26th May 2015) - Yuan, Bo; Liang, Yasha; Wang, Duoning; Luo, Fengming
<x xml:space="preserve">Abstract</x> Hepatocellular carcinoma (HCC) is among the leading causes of cancer‐related death in China. Deregulation of microRNA (miRNA) contributes to HCC development by influencing cell growth, apoptosis, migration or invasion. It has been proved that miR‐940 plays important roles in various cancers. Here we investigated the role of miR‐940 in HCC. We found that miR‐940 was remarkably decreased in HCC tissues and cell lines. Importantly, lower miR‐940 expression in HCC tissues significantly correlated with the reduced patient's survival rate. Overexpression of miR‐940 inhibited HCC cell line growth and induced cell apoptosis, and vice versa. Estrogen‐related receptor gamma (ESRRG) was targeted by miR‐940, and suppression of ESRRG inhibited HCC cell lines growth and induced cell apoptosis. In conclusion, we found that a lower level of miR‐940 in HCC promoted cellular proliferation via ESRRG, which may lead to the short survival period of HCC patients.